1990
DOI: 10.1007/978-1-4612-3444-9
|View full text |Cite
|
Sign up to set email alerts
|

Nonstandard Methods in Fixed Point Theory

Abstract: except for brief excerpts in connection with reviews or scholarly analysis. Use in connection with any form of information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed is forbidden. The use of general descriptive names, trade names, trademarks, etc., in this publication, even if the former are not especially identified, is not to be taken as a sign that such names, as understood by the 'frade Marks and Merchandise Mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
99
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 0 publications
1
99
0
Order By: Relevance
“…We say that X has asymptotic normal structure (with respect to the weak topology) [4], AN S (respectively, w-AN S) for short, if for each bounded closed (weakly compact) and convex subset C of X consisting of more than one point and each asymptotically regular sequence {x n } in C, there is a point x ∈ C such that lim inf n x − x n < diam (C) (see also [1,2,7,8,19,20,26,30,36]). …”
Section: The Asymptotic Normal Structure and The Semi-opial Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…We say that X has asymptotic normal structure (with respect to the weak topology) [4], AN S (respectively, w-AN S) for short, if for each bounded closed (weakly compact) and convex subset C of X consisting of more than one point and each asymptotically regular sequence {x n } in C, there is a point x ∈ C such that lim inf n x − x n < diam (C) (see also [1,2,7,8,19,20,26,30,36]). …”
Section: The Asymptotic Normal Structure and The Semi-opial Coefficientsmentioning
confidence: 99%
“…For more information about the connections between the above mentioned geometric properties of Banach spaces (and other ones) see [1,2,3,13,14,18,19,20,27,29,33,34,35,37,38,39,40].…”
Section: The Asymptotic Normal Structure and The Semi-opial Coefficientsmentioning
confidence: 99%
“…The asymptotic center of {x n } in C [13] is the set Ac (C, {x n }) = {x ∈ C : r a (x, {x n }) = r (C, {x n })} . For more details see [1], [16] and [17].…”
Section: Basic Notations and Factsmentioning
confidence: 99%
“…In a Banach space (X, · ) we denote by κ 0 (X) the infimum of the numbers κ (C) where C is a closed, convex, bounded and nonempty subset of X. It is known [2] , [16] (1) and 0 (X) < 1 if and only κ 0 (X) > 1 [12]. Therefore κ 0 (X) ≤ √ 2 [2].…”
Section: Basic Notations and Factsmentioning
confidence: 99%
“…In [14] Kirk, extending Browder's Theorem, showed that a weakly compact convex subset of a Banach space with normal structure has the fpp. In [2] Alspach exhibited a weakly compact convex subset K of the Lebesgue space L 1 [0,1] and an isometry T : K → K without a fixed point, proving, thereby, that the space L 1 [0, 1] does not have the fpp. However, in [19], Maurey, using the techniques of ultraproducts, showed that reflexive subspaces of L 1 [0, 1], as well as the sequence space c 0 , have the fpp.…”
Section: Introductionmentioning
confidence: 99%